A Primer on College Student Substance Use Disorders Screening, Assessment, and Treatment Planning. Issue 1 (2nd January 2018) - Cooper, Stewart E.
ABSTRACT: Significant numbers of college students experience negative consequences due to their misuse of alcohol and other drugs. For far too many, some of these effects are ruinous of their lives, and for well more than a thousand each year, life ending. This article first provides an overview of the scope of this problem. It then covers both assessment and intervention starting with brief and standard assessment inventories followed by a perspective on comprehensive focused counseling that incorporates an assessment of multiple life areas. A case is made that many students have substance use disorders issues either as primary problems or auxiliary to other concerns. Treatment planning based on a comprehensive approach to change, and the role of ongoing utilization of change measures, is then discussed. A basic premise of the article is that due to a lack of education, training, and exposure, many college mental health practitioners underdiagnose and underattend to the presence of substance use disorders problems. Many clinical staff members have never taken an academic course focused on this treatment issue or have done little by way of continuing education on this topic, so they may lack the knowledge, skills, and aptitudes related to the provision of helpful comprehensive care and consequently make the error of focusing exclusively on the substance use disorders related behaviors.